Changing trends in complications of chronic hepatitis C. (21st July 2017) - Lu, Mei; Li, Jia; Rupp, Loralee B.; Zhou, Yueren; Holmberg, Scott D.; Moorman, Anne C.; Spradling, Philip R.; Teshale, Eyasu H.; Boscarino, Joseph A.; Daida, Yihe G.; Schmidt, Mark A.; Trudeau, Sheri; et al.
Abstract: Background & Aims: Chronic hepatitis C virus (HCV)‐related complications have increased over the past decade. Methods: We used join‐point regression modelling to investigate trends in these complications from 2006 to 2015, and the impact of demographics on these trends. Using data from the Chronic Hepatitis Cohort Study (CHeCS), we identified points at which the trend significantly changed, and estimated the annual percent change (APC) in rates of cirrhosis, decompensated cirrhosis and all‐cause mortality, adjusted by race, sex and age. Results: Among 11, 167 adults with chronic HCV infection, prevalence of cirrhosis increased from 20.8% to 27.6% from 2006 to 2015, with adjusted annual percentage change (aAPC) of 1.2 ( p <. 01). Although incidence of all‐cause mortality increased from 1.8% in 2006 to 2.9% in 2015, a join‐point was identified at 2010, with aAPCs of 9.6 before (2006 < 2010; p < .01) and −5.2 after (2010 ≤ 2015; p < .01), indicating a decrease in mortality from 2010 and onward. Likewise, overall prevalence of decompensated cirrhosis increased from 9.3% in 2006 to 10.4% in 2015, but this increase was confined to patients 60 or older (aAPC = 1.5; p = .023). Asian American and Black/African American patients demonstrated significantly higher rates of cirrhosis than White patients, while older patients and men demonstrated higher rates of cirrhosis and mortality. Conclusions: Although cirrhosis and mortality among HCV‐infected patients in the US have increased over the past decade, all‐cause mortality has decreased in recent years.